Improving Stability in Developing Nations through Automation 2006. - Kopacek, Peter (Elsevier, 2007)
Technological development has caused profound changes and social stability. Regions which have had stable populations for centuries have experienced enormous population growth leading to the emergence of sometimes unmanageable megaplex cities as well as bringing about macroscopic environmental change.